Battery packing material, battery, manufacturing method for these, and polyester film

JP2025023244APending Publication Date: 2025-02-14DAI NIPPON PRINTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024210713
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-12-06
Filing Date
2024-12-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0014】 本発明によれば、ポリエステルフィルム層を最表面に備える電池用包装材料において、当該ポリエステルフィルム層の表面の印字適性に優れた電池用包装材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023244000006
    Figure 2025023244000006
  • Figure 2025023244000007
    Figure 2025023244000007
  • Figure 2025023244000008
    Figure 2025023244000008
Patent Text Reader

Abstract

To provide a battery packing material with excellent printability on the surface of a polyester film layer in the battery packing material including the polyester film layer on the outermost surface.SOLUTION: The battery packing material is composed of a laminate including at least a substrate layer located at an outermost surface, a barrier layer, and a heat-fusible resin layer in this order, The outermost surface of the substrate layer is composed of a polyester film layer. The following formula is satisfied when acquiring infrared absorption spectra in 18 directions from 0° to 170° in increments of 10°, for the surface of the polyester film layer, using the total reflection method of Fourier transform infrared spectroscopy. Ymax / Ymin<1.4.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging material for batteries, a battery, a method for producing the same, and a polyester film. [Background technology]

[0002] Various types of batteries have been developed, but in all batteries, packaging materials are essential components for sealing battery elements such as electrodes and electrolytes. Conventionally, metallic packaging materials have been widely used for battery packaging.

[0003] Meanwhile, in recent years, batteries are being required to have a variety of shapes and to be thin and lightweight in line with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. However, the metallic battery packaging materials that have been widely used in the past have the drawbacks of being difficult to keep up with the diversification of shapes and also having limitations in terms of weight reduction.

[0004] In recent years, a film-like laminate in which a substrate, a barrier layer, and a heat-sealable resin layer are laminated in this order has been proposed as a battery packaging material that can be easily processed into various shapes and can be made thinner and lighter (see, for example, Patent Document 1). In such battery packaging materials, generally, recesses are formed by cold forming, and battery elements such as electrodes and electrolyte are placed in the spaces formed by the recesses, and the heat-sealable resin layers are heat-sealed to each other to obtain a battery in which the battery elements are housed inside the battery packaging material.

[0005] In various packaging materials composed of the above-mentioned laminates, a method of printing on the packaging material (generally called reverse printing) is widely adopted by printing ink on the surface of the base layer to form a barcode, pattern, character, etc., and laminating an adhesive and a barrier layer on the printed side of the base layer. However, if such a printed surface exists between the base layer and the barrier layer, the adhesion between the base layer and the barrier layer decreases, and delamination is likely to occur between the layers. In particular, since high safety is required for batteries to which the battery packaging material is applied, such a method of printing by reverse printing is avoided for battery packaging materials. Therefore, in the past, when forming a print such as a barcode on a battery packaging material, a method of attaching a seal on which a print is formed to the surface of the base layer is generally adopted. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, when a sticker on which printing has been formed is attached to the surface of the base material layer, the thickness and weight of the battery packaging material increases. Therefore, in consideration of the recent trend toward thinner and lighter battery packaging materials, the present inventors have investigated a method of printing by printing ink directly onto the surface of the base material layer of the battery packaging material.

[0008] As a method of directly printing the surface of the base layer of the battery packaging material by printing ink, for example, pad printing (also called tampo printing) and inkjet printing are known. Pad printing is a printing method as follows. First, ink is poured into a recess of a flat plate in which a pattern to be printed is etched. Next, a silicon pad is pressed against the recess to transfer the ink to the silicon pad. Next, the ink transferred to the surface of the silicon pad is transferred to the printing object to form a print on the printing object. Such pad printing has the advantage that since the ink is transferred to the printing object using an elastic silicon pad or the like, it is easy to print on the surface of the battery packaging material after molding, and the battery can be printed after the battery element is sealed with the battery packaging material. Inkjet printing also has the same advantage.

[0009] However, the inventors have conducted research and found that in a battery packaging material having a polyester film layer on the outermost surface, when ink is printed on the surface of the polyester film layer, the ink does not spread properly on the surface of the polyester film layer and the dots in the printed area formed by the ink tend to be irregular in shape, making it difficult to form a print of the desired size and shape.

[0010] Under these circumstances, a main object of the present invention is to provide a battery packaging material having a polyester film layer on the outermost surface, the surface of which has excellent printability. [Means for solving the problem]

[0011] The present inventors have conducted extensive research to solve the above problems. As a result, they have found that a battery packaging material that is composed of a laminate including at least a substrate layer, a barrier layer, and a heat-sealable resin layer located on the outermost surface in this order, the outermost surface of the substrate layer being composed of a polyester film layer, and that satisfies the following formula when infrared absorption spectra are obtained for the surface of the polyester film layer in 18 directions at 10° intervals from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy, exhibits excellent printability by suppressing inappropriate spreading of ink on the surface of the polyester film layer and preventing dots in a printed portion from becoming distorted in shape. Y max / Y min <1.4 Y max In each of the 18 directions, the infrared absorption spectrum wave number is 134. 0cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the maximum value among the values ​​divided by. Y min In each of the 18 directions, the infrared absorption spectrum wave number is 134. 0cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by. Maximum Y max and the minimum value Y min In the calculation of 1340 / Y 1410 From these, the maximum value Y max and the minimum value Y min Select .

[0012] The present invention was completed based on these findings and through further investigation.

[0013] That is, the present invention provides the following aspects. Item 1. The laminate is made of at least a substrate layer located on the outermost surface, a barrier layer, and a heat-sealable resin layer in this order, The outermost surface of the base layer is constituted by a polyester film layer, A battery packaging material that satisfies the following formula when infrared absorption spectra are obtained for the surface of the polyester film layer in 18 directions at 10° increments from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy. Y max / Y min <1.4 Y max In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the maximum value among the values ​​divided by. Y min In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by. Item 2. The battery packaging material according to Item 1, which is used in applications in which printing is performed on the surface of the polyester film layer. Item 3. The battery packaging material according to Item 1 or 2, wherein the polyester film layer has a surface with an arithmetic average roughness Ra of 10 nm or more, as measured in accordance with the method specified in JIS B 0601-2001. Item 4. An adhesive layer is provided between the barrier layer and the thermally adhesive resin layer, Item 4. The battery packaging material according to any one of Items 1 to 3, wherein the adhesive layer contains an acid-modified polyolefin. Item 5. The acid-modified polyolefin of the adhesive layer is maleic anhydride-modified polypropylene, Item 5. The battery packaging material according to item 4, wherein the heat-sealable resin layer contains polypropylene. Item 6. The battery packaging material according to any one of Items 4 to 5, wherein the adhesive layer is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group. Item 7. The battery packaging material according to any one of Items 4 to 6, wherein the adhesive layer is a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C═N bond, and a COC bond. Item 8. The battery packaging material according to any one of Items 4 to 7, wherein the adhesive layer contains at least one resin selected from the group consisting of a urethane resin, an ester resin, and an epoxy resin. Item 9. The battery packaging material according to any one of Items 4 to 8, wherein the adhesive layer has a thickness of 50 μm or less. Item 10. The battery packaging material according to any one of Items 4 to 8, wherein the adhesive layer has a thickness of 10 μm or more and 50 μm or less. Item 11. The battery packaging material according to any one of Items 4 to 10, which is a co-extrusion laminate of the adhesive layer and the heat-sealable resin layer. Item 12. The battery packaging material according to any one of Items 1 to 11, wherein the polyester film layer has a thickness of 10 μm or more and 50 μm or less. Item 13. The battery packaging material according to any one of Items 1 to 12, wherein the polyester film layer is composed of a stretched polyester film. Item 14. The battery packaging material according to any one of Items 1 to 13, wherein when infrared absorption spectra are obtained for the surface of the polyester film layer in 18 directions at 10° intervals from 0° to 170° using a total reflection method of Fourier transform infrared spectroscopy, the following formula is satisfied: 1.1≦Y max / Y min <1.4 Item 15. At least one surface of the barrier layer is provided with an acid-resistant coating, When the acid-resistant film was analyzed using time-of-flight secondary ion mass spectrometry, it was found that CePO 4+, CePO 4- , CrPO 2+ , and CrPO 4- At least one selected from the group consisting of Item 15. The packaging material for a battery according to any one of Items 1 to 14, wherein a peak derived from at least one species is detected. Item 16. The battery packaging material according to any one of Items 1 to 15, wherein at least one surface of the barrier layer is provided with an acid-resistant coating film containing at least one compound selected from the group consisting of phosphorus compounds, chromium compounds, fluorides, and triazine thiol compounds. Item 17. The packaging material for batteries according to any one of Items 1 to 16, wherein at least one surface of the barrier layer is provided with an acid-resistant coating containing a cerium compound. Item 18. The battery packaging material according to any one of Items 1 to 17, wherein a lubricant is present in at least one of the interior and the surface of the polyester film layer. Item 19. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the battery packaging material according to any one of Items 1 to 18. Item 20. The battery according to item 19, wherein the polyester film layer has a printed portion on its surface. Item 21. A battery comprising: a packaging step of housing a battery element including at least a positive electrode, a negative electrode, and an electrolyte in a package made of the battery packaging material according to any one of items 1 to 18; a step of printing a surface of the polyester film layer at least either before or after the storing step; A method for manufacturing a battery comprising the steps of: Item 22. A polyester film for use in the polyester film layer located on the outermost surface of a battery packaging material, A polyester film, which satisfies the following formula when infrared absorption spectra are obtained for a surface of the polyester film in 18 directions at 10° increments from 0° to 170° using a total reflection method of Fourier transform infrared spectroscopy. Y max / Y min <1.4 Y maxIn each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the maximum value among the values ​​divided by. Y min In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by. Item 23. Use of a polyester film that satisfies the following formula when infrared absorption spectra are obtained in 18 directions at 10° intervals from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy for the surface of the polyester film, as a polyester film layer located on the outermost surface of a packaging material for batteries. Y max / Y min <1.4 Y max In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the maximum value among the values ​​divided by. Y min In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by. Effect of the Invention

[0014] According to the present invention, it is possible to provide a battery packaging material having a polyester film layer on the outermost surface, the surface of which has excellent printability. [Brief description of the drawings]

[0015] [Figure 1] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 2] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 3] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Figure 4] 1 is an image of a printed portion formed on a surface of a biaxially stretched polyethylene terephthalate film in Example 2, observed with a laser microscope. [Diagram 5] 1 is an image of a printed portion formed on the surface of a biaxially stretched polyethylene terephthalate film of Comparative Example 7, observed with a laser microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The battery packaging material of the present invention is composed of a laminate having at least a base material layer located on the outermost surface, a barrier layer, and a heat-sealable resin layer in this order, the outermost surface of the base material layer being composed of a polyester film layer, and is characterized in that when infrared absorption spectra are obtained in 18 directions at 10° intervals from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy, the following formula is satisfied: The battery packaging material of the present invention will be described in detail below. Y max / Y min <1.4 In the above formula, Y max In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 (CH2 vertical vibration) with a wave number of 1410 cm -1 Absorption peak intensity Y 1410 This is the maximum value among the values ​​divided by (C=C stretching vibration). Y minIn each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by. Maximum Y max and the minimum value Y min In the calculation of 1340 / Y 1410 From these, the maximum value Y max and the minimum value Y min Select .

[0017] The battery packaging material of the present invention will be described in detail below. In this specification, the numerical range indicated by "to" means "not less than" or "not more than." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0018] 1.Laminated structure of battery packaging material The battery packaging material of the present invention is composed of a laminate including, in this order, a substrate layer 1 located on the outermost surface, a barrier layer 3, and a heat-sealable resin layer 4, as shown in Fig. 1 for example. The outermost surface of the substrate layer 1 is composed of a polyester film layer. In the battery packaging material of the present invention, the polyester film layer is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. That is, when the battery is assembled, the heat-sealable resin layers 4 located on the periphery of the battery element are heat-sealed to each other to seal the battery element, thereby sealing the battery element.

[0019] As described later, the base layer 1 may have other layers in addition to the polyester film layer. When the base layer 1 has the other layers, the polyester film layer and the other layers may be bonded by an adhesive layer. The battery packaging material of the present invention may have an adhesive layer 2 between the base layer 1 and the barrier layer 3, as shown in FIG. 2, for example, if necessary, in order to enhance adhesion therebetween. An adhesive layer 5 may be provided between the barrier layer 3 and the heat-sealable resin layer 4, as necessary, in order to enhance adhesion therebetween.

[0020] The total thickness of the laminate constituting the battery packaging material of the present invention is not particularly limited, but from the viewpoint of improving formability while making the total thickness of the laminate as thin as possible, it is preferably about 180 μm or less, more preferably about 35 to 160 μm, and even more preferably about 45 to 150 μm.

[0021] The battery packaging material of the present invention can be suitably used in applications where printing is performed on the surface of the polyester film layer located on the outermost surface. As the printing with ink, for example, the above-mentioned pad printing and inkjet printing are suitable, and inkjet printing is particularly suitable. As the solvent contained in the ink, methyl ethyl ketone, acetone, isopropyl alcohol, ethanol, etc. are preferably included. The solvent may be used alone or in combination of two or more kinds.

[0022] 2. Layers that form the battery packaging material [Base material layer 1] In the battery packaging material of the present invention, the base layer 1 is the layer located at the outermost surface. The outermost surface of the base layer 1 is composed of a polyester film layer. In the present invention, even when a lubricant is present on the surface of the polyester film layer, the polyester film layer to which the lubricant is attached constitutes the outermost surface of the battery packaging material. Therefore, even in the case of the base layer 1 having a lubricant present on its surface, the base layer 1 is the layer located at the outermost surface of the battery packaging material.

[0023] In the battery packaging material of the present invention, the polyester film layer constituting the outermost surface is characterized in that, when infrared absorption spectra are obtained for the surface of the polyester film layer in 18 directions at 10° increments from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy, the following formula is satisfied: Y max / Y min <1.4 Y max In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the maximum value among the values ​​divided by. Also, Y min In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by. Maximum Y max and the minimum value Y min In the calculation of 1340 / Y 1410 From these, the maximum value Y max and the minimum value Y min Select .

[0024] In the battery packaging material of the present invention, the outermost surface of the base layer is composed of a polyester film layer, and the polyester film layer has the above-mentioned specific surface orientation degree, so that excellent printability is exhibited even though the outermost surface is composed of a polyester film. For example, the mechanism of this can be considered as follows. That is, in the battery packaging material of the present invention, since the polyester film layer constituting the outermost surface has the above-mentioned specific surface orientation degree, it can be said that the orientation degree of the polyester molecules in the polyester film layer is low. For this reason, it is considered that the ink is likely to spread in a uniform direction on the surface of the polyester film layer, and excellent printability is exhibited. In conventional battery packaging materials, when a polyester film layer is used as the base layer, a polyester film with a high degree of orientation of the polyester molecules was used by greatly stretching the polyester film from the viewpoint of improving formability, etc., but in the present invention, the polyester film layer constituting the outermost surface has the above-mentioned surface orientation degree, so that excellent printability is exhibited. There are methods for improving printability by adding a lubricant to the surface of the base layer or by subjecting the base layer to a surface treatment, and these methods can be adopted in the present invention. However, in the present invention, since the polyester film layer has the above-mentioned specific degree of surface orientation, excellent printability is exhibited even though the outermost surface is composed of a polyester film.

[0025] Specific conditions for measuring the infrared absorption spectrum are as follows: The infrared absorption spectrum of the surface of the polyester film layer can be measured in a state where it is laminated on a battery packaging material.

[0026] (Infrared absorption spectrum measurement conditions) Spectrometer (single reflection ATR accessory included) Detector: MCT (Hg Cd Te) Wavenumber resolution: 8cm -1 Number of times accumulated: 128 times IRE:Ge Incident angle: 30° Polarizer: Wire grid, S-polarized Baseline: Wavenumber 1800-2000cm -1 Average intensity in the range Wave number 1340cm -1 Absorption peak intensity Y 1340 : Wave number 1335~1342cm -1 Maximum peak intensity in the range minus the baseline value Wave number 1410cm -1 Absorption peak intensity Y 1410 : Wave number 1400~1410cm -1 Maximum peak intensity in the range minus the baseline value

[0027] To obtain infrared absorption spectra in 18 directions, the sample with the exposed polyester film is placed horizontally on the sample holder and rotated by 10° with the Ge crystal placed on top of the sample. The incidence angle is the angle between the perpendicular (normal) line and the incident light.

[0028] From the viewpoint of improving the printability of battery packaging materials, the surface orientation degree (Y max / Y min ), the upper limit is less than 1.4. The upper limit is preferably about 1.3 or less, and the lower limit is preferably about 1.0 or more, more preferably about 1.1 or more, and even more preferably about 1.2 or more. Preferred ranges include about 1.0 or more and less than 1.4, about 1.0 to 1.3, about 1.1 or more and less than 1.4, about 1.1 to 1.3, about 1.2 or more and less than 1.4, and about 1.2 to 1.3. max / Y min ) is about 1.1 or more, the printability of the battery packaging material can be improved and the moldability can be suitably improved.

[0029] The degree of surface orientation as described above: Y max / Y minThe polyester film having the above formula (1) can be produced by appropriately adjusting the stretching method, stretching ratio, stretching speed, cooling temperature, heat setting temperature, and the like when producing the polyester film.

[0030] In addition, in the battery packaging material of the present invention, the arithmetic mean roughness Ra of the polyester film layer constituting the outermost surface is, from the viewpoint of improving the printability of the battery packaging material, preferably about 1000 nm or less, more preferably about 500 nm or less as an upper limit, and preferably about 10 nm or more, more preferably about 20 nm or more as a lower limit, and preferably within a range of about 10 to 1000 nm, or about 20 to 500 nm.

[0031] The arithmetic mean roughness Ra of the polyester film layer constituting the outermost surface is a value determined for the surface of the polyester film layer in accordance with the method specified in JIS B 0601-2001. A specific measurement method can be adopted as described in the Examples. The arithmetic mean roughness Ra of the polyester film layer can be measured in a state where it is laminated on the battery packaging material.

[0032] The arithmetic mean roughness Ra of the surface of the polyester film layer can be adjusted by the height and density of the unevenness of the surface of the cooling roll when producing the polyester film. The polyester film layer may contain additives (flame retardant, antiblocking agent, antioxidant, light stabilizer, tackifier, antistatic agent, etc.) as particles, which may be used to adjust the arithmetic mean roughness Ra. The average particle size of the particles may be, for example, about 0.1 to 5 μm, and the content of the particles may be, for example, about 0.01 to 0.1 mass %.

[0033] Specific examples of polyesters constituting the polyester film layer include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit, copolymerized polyesters mainly composed of butylene terephthalate as a repeating unit, etc. Specific examples of copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit include copolymerized polyesters mainly composed of ethylene terephthalate as a repeating unit polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decane dicarboxylate), etc. Specific examples of copolymer polyesters containing butylene terephthalate as the main repeating unit include copolymer polyesters in which butylene terephthalate as the main repeating unit is polymerized with butylene isophthalate (hereinafter abbreviated as polybutylene (terephthalate / isophthalate)), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters may be used alone or in combination of two or more. Polyesters have the advantages of excellent heat resistance and electrolyte resistance, and are unlikely to cause whitening or the like when an electrolyte is attached, and are therefore preferably used as a material for forming the base layer 1.

[0034] The polyester film layer may be either a stretched polyester film or an unstretched polyester film, but from the viewpoint of suitably improving the formability of the battery packaging material, it is preferably a stretched polyester film, more preferably a biaxially stretched polyester film, and more preferably a biaxially stretched polyethylene terephthalate film. The stretching method may be, for example, a sequential biaxial stretching method, an inflation method, or a simultaneous biaxial stretching method.

[0035] The thickness of the polyester film layer is not particularly limited, but from the viewpoint of thinning the battery packaging material while improving formability, the upper limit is, for example, about 50 μm or less, preferably about 30 μm or less, and more preferably about 25 μm or less; the lower limit is preferably about 1 μm or more, more preferably about 5 μm or more, and even more preferably about 10 μm or more; and preferred ranges include about 1 to 50 μm, about 1 to 30 μm, about 1 to 25 μm, about 5 to 50 μm, about 5 to 30 μm, about 5 to 25 μm, about 10 to 50 μm, about 10 to 30 μm, and about 10 to 25 μm.

[0036] The polyester film layer may be a single layer or a multi-layer (multi-layer structure). When the polyester film layer is a multi-layer, it is sufficient that at least the polyester film located on the outermost layer side (the side opposite to the barrier layer 3) satisfies the above-mentioned surface orientation degree, and the other polyester films have a surface orientation degree of Y. max / Y min may be 1.4 or more.

[0037] In addition, for the purpose of improving the formability of the battery packaging material, the base material layer 1 can also be formed by laminating (forming a multi-layer structure) at least one of a resin film and a coating made of a material different from polyester on the barrier layer side of the polyester film layer in addition to the polyester film layer.

[0038] Examples of other resin films that can be used for the base layer 1 include resin films made of polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, and mixtures or copolymers thereof. A specific example of a laminated structure of a polyester film and a resin film made of a different material is a multilayer structure in which a polyester film layer and a polyamide film layer are laminated.

[0039] Specific examples of polyamide films constituting the polyamide film layer include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 6,6; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid; polyamide MXD6 (polymetaxylylene adipamide, etc.); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); and further, polyamides containing lactam components and 4,4'-diphenylmethane ... Examples of the polyamide include polyamides copolymerized with an isocyanate component such as isocyanate, polyesteramide copolymers and polyetheresteramide copolymers, which are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols, and polyamide films of these copolymers. These polyamide films may be used alone or in combination of two or more. Polyamide films have excellent stretchability and can prevent whitening due to resin cracking during molding, and are preferably used as a resin film for the base layer 1 together with polyester films.

[0040] Specific examples of the case where the base layer 1 has a multi-layer structure of polyester film and the case where the other resin film is provided include a laminate of polyester film and nylon film, and a laminate of multiple polyester films, and more preferably a laminate of stretched polyester film and stretched nylon film, and a laminate of multiple stretched polyester films. For example, when the base layer 1 has a two-layer structure, it is preferable to have a configuration in which a polyester film and a polyamide film are laminated, or a configuration in which a polyester film and a polyester film are laminated, and it is more preferable to have a configuration in which polyethylene terephthalate and nylon are laminated, or a configuration in which polyethylene terephthalate and polyethylene terephthalate are laminated. In addition, polyester films are unlikely to discolor when, for example, an electrolyte solution adheres to the surface, and in the battery packaging material of the present invention, the polyester film layer constitutes the outermost surface, so that the configuration can be excellent in electrolyte resistance.

[0041] When the base layer 1 has a multilayer structure, the thickness of the polyester film that is not the outermost layer and the resin film other than the polyester film preferably has a lower limit of about 3 μm or more, and more preferably about 5 μm or more, and preferably has an upper limit of about 30 μm or less, and preferably about 25 μm or less, and preferred ranges are about 3 to 30 μm, about 3 to 25 μm, about 5 to 30 μm, and about 5 to 25 μm.

[0042] When the base layer 1 has a multi-layer structure, the polyester film and each resin film may be bonded via an adhesive, or may be directly laminated without an adhesive. When bonding without an adhesive, for example, a method of bonding in a thermally molten state such as a co-extrusion method, a sandwich lamination method, or a thermal lamination method may be mentioned. When bonding via an adhesive, the adhesive used may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the bonding mechanism of the adhesive is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, an electron beam curing type, an ultraviolet ray curing type, and the like. Specific examples of the adhesive include the same adhesives as those exemplified in the adhesive layer 2. The thickness of the adhesive may also be the same as that of the adhesive layer 2.

[0043] In addition, when the base layer 1 has a multi-layer structure, the adhesive for bonding the polyester film and each resin film is preferably a resin composition containing a modified thermoplastic resin graft-modified with an unsaturated carboxylic acid derivative component. The modified thermoplastic resin is preferably a resin obtained by modifying a polyolefin, a styrene-based elastomer, a polyester-based elastomer, or the like with an unsaturated carboxylic acid derivative component. The resin may be used alone or in combination of two or more types. In addition, the unsaturated carboxylic acid derivative component may be an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, or the like. The unsaturated carboxylic acid derivative component may be used alone or in combination of two or more types.

[0044] Examples of polyolefins in the modified thermoplastic resin include low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-α-olefin copolymers, homo-, block- or random polypropylenes, propylene-α-olefin copolymers, copolymers of the above materials with polar molecules such as acrylic acid or methacrylic acid, crosslinked polyolefins, etc. The polyolefins may be one type alone or two or more types in combination.

[0045] The styrene-based elastomer in the modified thermoplastic resin may be a copolymer of styrene (hard segment) and butadiene or isoprene or a hydrogenated product thereof (soft segment). The polyolefin-based resin may be a single type or a combination of two or more types.

[0046] The polyester-based elastomer in the modified thermoplastic resin may be a copolymer of a crystalline polyester (hard segment) and a polyalkylene ether glycol (soft segment), etc. The polyolefin may be one type alone or two or more types in combination.

[0047] Examples of the unsaturated carboxylic acid in the modified thermoplastic resin include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic acid. Examples of the acid anhydrides of unsaturated carboxylic acids include maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, and bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylic anhydride. Examples of the esters of unsaturated carboxylic acids include esters of unsaturated carboxylic acids such as methyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, dimethyl maleate, monomethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citraconic acid, dimethyl tetrahydrophthalate, and dimethyl bicyclo[2,2,1]hept-2-ene-5,6-dicarboxylate.

[0048] The modified thermoplastic resin can be obtained by heating and reacting about 0.2 to 100 parts by mass of the unsaturated carboxylic acid derivative component with 100 parts by mass of a base thermoplastic resin in the presence of a radical initiator.

[0049] The reaction temperature is preferably about 50 to 250° C., more preferably about 60 to 200° C. The reaction time depends on the production method, but in the case of melt graft reaction using a twin-screw extruder, it is preferably about 2 to 30 minutes, which is within the residence time of the extruder, more preferably about 5 to 10 minutes. The modification reaction can be carried out under either normal pressure or pressurized conditions.

[0050] The radical initiator used in the modification reaction includes organic peroxides. As the organic peroxide, various materials can be selected depending on the temperature conditions and the reaction time, and examples thereof include alkyl peroxides, aryl peroxides, acyl peroxides, ketone peroxides, peroxyketals, peroxycarbonates, peroxyesters, and hydroperoxides. In the case of the melt graft reaction using the above-mentioned twin-screw extruder, alkyl peroxides, peroxyketals, and peroxyesters are preferred, and di-t-butyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxy-hexyne-3, and dicumyl peroxide are more preferred.

[0051] When the base layer 1 has a multi-layer structure, the thickness of the adhesive layer located between the polyester film or each resin film is preferably about 0.1 to 5 μm, more preferably about 0.5 to 3 μm. The adhesive layer may contain the same colorant as the adhesive layer 2 described below.

[0052] In the present invention, from the viewpoint of improving the formability of the battery packaging material, it is preferable that a lubricant is present in at least one of the inside and the surface of the polyester film layer. That is, the lubricant may be contained in the polyester film layer, or the lubricant may be present on the surface of the battery packaging material. In addition, the lubricant present on the surface of the polyester film layer may be a lubricant that is exuded from the polyester film layer, or a lubricant that is applied to the surface of the polyester film layer.

[0053] The lubricant is not particularly limited, but preferably includes amide-based lubricants and silicone-based lubricants. Specific examples of lubricants include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide. Specific examples include ethylene bisoleamide, ethylene biserucamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacamide. Specific examples of fatty acid ester amides include stearamide ethyl stearate. Specific examples of aromatic bisamides include m-xylylene bisstearamide, m-xylylene bishydroxystearamide, and N,N'-distearyl isophthalamide. Specific examples of cyano ester amides include ethyl stearate, m-xylylene bishydroxystearamide, and N,N'-distearyl isophthalamide. As the silicone-based lubricant, non-reactive modified silicone oils such as alkyl-modified silicone oil, higher fatty acid ester-modified silicone oil, polyether-modified silicone oil, etc. are preferable. The lubricant may be used alone or in combination of two or more kinds.

[0054] When a lubricant is present on the surface of the polyester film layer, the amount of the lubricant is not particularly limited. From the viewpoint of exhibiting excellent printability, the amount of the lubricant is preferably about 3 mg / m. 2 That's all. More preferably, 3 to 15 mg / m 2 about, more preferably 4 to 14 mg / m 2 In addition, even when a lubricant is present on the surface of the polyester film layer, the above-mentioned infrared absorption spectrum can be measured for the surface of the polyester film layer on which the lubricant is present.

[0055] Furthermore, additives such as flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present in at least one of the interior and surface of the base material layer 1. The additives may be used alone or in combination of two or more.

[0056] The thickness (total thickness) of the base layer 1 is not particularly limited, but from the viewpoint of thinning the battery packaging material while improving its formability, the upper limit is, for example, about 50 μm or less, and preferably about 40 μm or less, and the lower limit is preferably about 3 μm or more, more preferably about 5 μm or more, and even more preferably about 10 μm or more, and preferred ranges for the thickness of the base layer 1 include about 3 to 50 μm, about 3 to 40 μm, about 5 to 50 μm, about 5 to 40 μm, about 10 to 50 μm, and about 10 to 40 μm.

[0057] [Adhesive layer 2] In the battery packaging material of the present invention, the adhesive layer 2 is a layer that is provided between the base material layer 1 and the barrier layer 3, as necessary, in order to firmly bond them together.

[0058] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the adhesion mechanism of the adhesive used to form the adhesive layer 2 is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like.

[0059] Specific examples of adhesive components that can be used to form the adhesive layer 2 include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyether adhesives; polyurethane adhesives; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins such as polyolefins, carboxylic acid-modified polyolefins, and metal-modified polyolefins; polyvinyl acetate; cellulose adhesives; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred.

[0060] The polyurethane adhesive is a polyurethane adhesive containing a base agent containing a polyol component (A) and a curing agent containing a polyisocyanate component (B), the polyol component (A) contains a polyester polyol (A1), the polyester polyol (A1) is a polyester polyol composed of a polybasic acid component and a polyhydric alcohol component and having a number average molecular weight of 5,000 to 50,000, the polybasic acid component contains 45 to 95 mol % of an aromatic polybasic acid component in 100 mol %, and the adhesive layer has a tensile stress of 100 kg / cm at 100% elongation. 2 More than 500kg / cm 2Also included is a polyurethane adhesive for battery packaging material containing a base agent and a polyisocyanate curing agent, the base agent containing a polyol component (A) containing 5 to 50% by weight of a polyester polyol (A1) having a glass transition temperature of 40°C or higher and 95 to 50% by weight of a polyester polyol (A2) having a glass transition temperature of less than 40°C, and a silane coupling agent (B), and an equivalent ratio [NCO] / ([OH]+[COOH]) of the isocyanate groups contained in the curing agent to the total of the hydroxyl groups and carboxyl groups derived from the polyol component (A) is 1 to 30.

[0061] Further examples include adhesives containing a resin containing either one ((A) or (B)) of one or more resins (A) selected from the group consisting of modified polypropylene and acrylic resins, or a coupling agent (B) containing at least one of a silane coupling agent and a titanate-based coupling agent.

[0062] The adhesive layer 2 may also contain a colorant. When the adhesive layer 2 contains a colorant, the battery packaging material can be colored. As the colorant, known colorants such as pigments and dyes can be used. The colorant may be used alone or in combination of two or more types.

[0063] For example, specific examples of inorganic pigments preferably include carbon black and titanium oxide.Specific examples of organic pigments preferably include azo pigments, phthalocyanine pigments, and condensed polycyclic pigments.Examples of azo pigments include soluble pigments such as Watching Red and Carmine 6C; insoluble azo pigments such as monoazo yellow, disazo yellow, pyrazolone orange, pyrazolone red, and permanent red.Examples of phthalocyanine pigments include copper phthalocyanine pigments and metal-free phthalocyanine pigments such as blue pigments and green pigments.Examples of condensed polycyclic pigments include dioxazine violet and quinacridone violet.Examples of pigments that can be used include pearl pigments and fluorescent pigments.

[0064] Among colorants, carbon black is preferred in order to give the battery packaging material a black appearance, for example.

[0065] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0066] The content of the pigment in the adhesive layer 2 is not particularly limited as long as it colors the battery packaging material, and may be, for example, about 5 to 60 mass %.

[0067] The thickness of the adhesive layer 2 is not particularly limited as long as it functions as an adhesive layer, but may be, for example, about 1 to 10 μm, and preferably about 2 to 5 μm.

[0068] [Colored layer] The colored layer is a layer (not shown) that is provided as necessary between the base material layer 1 and the adhesive layer 2. By providing the colored layer, the battery packaging material can be colored.

[0069] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1 or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.

[0070] Specific examples of the colorant contained in the colored layer include the same as those exemplified in the section [Adhesive layer 2].

[0071] [Barrier layer 3] In the battery packaging material, the barrier layer 3 is a layer that has the function of preventing water vapor, oxygen, light, and the like from penetrating into the inside of the battery, in addition to improving the strength of the battery packaging material. The barrier layer 3 can be formed of a metal foil, a metal vapor deposition film, an inorganic oxide vapor deposition film, a carbon-containing inorganic oxide vapor deposition film, a film provided with these vapor deposition layers, and the like, and is preferably a layer formed of a metal. Specific examples of metals constituting the barrier layer 3 include aluminum, stainless steel, and titanium steel, and preferably aluminum or stainless steel. The barrier layer 3 is preferably formed of a metal foil, and more preferably formed of an aluminum alloy foil or stainless steel foil.

[0072] From the viewpoint of preventing the occurrence of wrinkles or pinholes in the barrier layer 3 during the production of the battery packaging material, it is more preferable that the barrier layer be formed from a soft aluminum foil such as annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O).

[0073] Examples of the stainless steel foil include austenitic stainless steel foil, ferritic stainless steel foil, etc. The stainless steel foil is preferably made of austenitic stainless steel.

[0074] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred.

[0075] The thickness of the barrier layer 3 is not particularly limited as long as it functions as a barrier layer against water vapor, etc., but from the viewpoint of reducing the thickness of the battery packaging material, the upper limit is preferably about 85 μm or less, more preferably about 50 μm or less, and even more preferably 45 μm or less, and the lower limit is preferably about 10 μm or more, and the thickness range can be, for example, about 10 to 85 μm, preferably about 10 to 50 μm, and more preferably about 10 to 45 μm. When the barrier layer 3 is made of stainless steel foil, the thickness of the stainless steel foil is preferably about 85 μm or less, more preferably about 50 μm or less, more preferably about 40 μm or less, even more preferably about 30 μm or less, and particularly preferably about 25 μm or less, and the lower limit is about 10 μm or more, and the preferred thickness range is about 10 to 85 μm, about 10 to 50 μm, more preferably about 10 to 40 μm, more preferably about 10 to 30 μm, and even more preferably about 15 to 25 μm.

[0076] In addition, it is preferable that at least one surface, preferably both surfaces, of the barrier layer 3 are chemically treated in order to stabilize adhesion and prevent dissolution and corrosion. Here, the chemical conversion treatment refers to a treatment for forming an acid-resistant film on the surface of the barrier layer. When an acid-resistant film is formed on the surface of the barrier layer 3 of the present invention, the barrier layer 3 includes the acid-resistant film. Examples of the chemical conversion treatment include a chromate treatment using a chromate compound such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate; a chromate treatment using a phosphoric acid compound such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid; and a chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.

[0077] [ka]

[0078] [ka]

[0079] [ka]

[0080] [ka]

[0081] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2 Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2The alkyl group and the hydroxyalkyl group represented by the formulas may be the same or different. In the formulas (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the formulas (1) to (4) is, for example, preferably 500 to 1,000,000, and more preferably 1,000 to 20,000.

[0082] As a chemical conversion treatment method for imparting corrosion resistance to the barrier layer 3, a method is exemplified in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at 150° C. or higher to form an acid-resistant film on the surface of the barrier layer 3. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be further formed on the acid-resistant film. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. These crosslinking agents may be used alone or in combination of two or more.

[0083] As a specific method for providing an acid-resistant film, for example, at least the inner layer side of the aluminum foil (barrier layer) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then a treatment liquid (aqueous solution) mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid (aqueous solution) mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid (aqueous solution) composed of a mixture of these and an aqueous synthetic resin such as an acrylic resin, a phenolic resin, or a polyurethane, can be applied to the degreased surface by a known coating method such as a roll coating method, a gravure printing method, or a dipping method to form an acid-resistant film. For example, when treated with a Cr (chromium) phosphate-based treatment liquid, CrPO4 (chromium phosphate), AlPO4 (aluminum phosphate), Al2O3 (aluminum oxide), Al(OH) x (Aluminum hydroxide), AlF x When treated with a zinc phosphate salt treatment solution, the resulting film is an acid-resistant film made of Zn2PO4·4H2O (zinc phosphate hydrate), AlPO4 (aluminum phosphate), Al2O3 (aluminum oxide), Al(OH) x (Aluminum hydroxide), AlF x It becomes an acid-resistant coating made of aluminum fluoride and other materials.

[0084] As another example of a specific method for providing an acid-resistant coating, for example, at least the inner layer surface of the aluminum foil is first degreased by a well-known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is subjected to a well-known anodizing treatment, thereby forming an acid-resistant coating.

[0085] Other examples of acid-resistant coatings include coatings of phosphorus compounds (e.g., phosphate-based) and chromium compounds (chromate-based). Phosphate-based coatings include zinc phosphate, iron phosphate, manganese phosphate, calcium phosphate, and chromium phosphate, while chromate-based coatings include chromium chromate.

[0086] Other examples of acid-resistant coatings include those made of phosphates, chromates, fluorides, triazine thiol compounds, etc., which prevent delamination between the aluminum and the base layer during embossing, prevent dissolution and corrosion of the aluminum surface, particularly aluminum oxide present on the aluminum surface, caused by hydrogen fluoride produced by a reaction between an electrolyte and water, and improve the adhesion (wettability) of the aluminum surface, preventing delamination between the base layer and aluminum during heat sealing, and in the case of embossed types, preventing delamination between the base layer and aluminum during press molding. Among the substances that form acid-resistant coatings, an aqueous solution composed of three components, phenol resin, chromium fluoride (3) compound, and phosphoric acid, is applied to the aluminum surface and then dried and baked.

[0087] The acid-resistant coating may include a layer having cerium oxide, phosphoric acid or a phosphate, an anionic polymer, and a crosslinking agent that crosslinks the anionic polymer, and the phosphoric acid or the phosphate may be blended in an amount of 1 to 100 parts by mass per 100 parts by mass of the cerium oxide. It is preferable that the acid-resistant coating has a multilayer structure further including a layer having a cationic polymer and a crosslinking agent that crosslinks the cationic polymer.

[0088] Furthermore, the anionic polymer is preferably poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, and the crosslinking agent is preferably at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent.

[0089] The phosphoric acid or the phosphate is preferably a condensed phosphoric acid or a condensed phosphate.

[0090] The chemical conversion treatment may be performed using only one type of chemical conversion treatment, or may be performed using a combination of two or more types of chemical conversion treatments. Furthermore, these chemical conversion treatments may be performed using one type of compound alone, or may be performed using a combination of two or more types of compounds. Among the chemical conversion treatments, chromate treatment with chromate acid, a combination of a chromate compound, a phosphoric acid compound, and an aminated phenol polymer, and the like are preferred.

[0091] Specific examples of the acid-resistant coating include those containing at least one of phosphorus compounds (phosphates, etc.), chromium compounds (chromates), fluorides, and triazine thiol compounds. Acid-resistant coatings containing cerium compounds are also preferred. As the cerium compound, cerium oxide is preferred.

[0092] Specific examples of the acid-resistant film include a phosphate-based film, a chromate-based film, a fluoride-based film, and a triazine thiol compound film. The acid-resistant film may be one of these films, or a combination of two or more of them. Furthermore, the acid-resistant film may be formed by degreasing the chemically treated surface of the barrier layer, using a treatment liquid made of a mixture of a metal phosphate and a water-based synthetic resin, or a treatment liquid made of a mixture of a nonmetal phosphate and a water-based synthetic resin.

[0093] The composition of the acid-resistant film can be analyzed, for example, by using time-of-flight secondary ion mass spectrometry. By analyzing the composition of the acid-resistant film using time-of-flight secondary ion mass spectrometry, for example, secondary ions consisting of Ce, P, and O (for example, Ce2PO4 + , CePO4 - N At least one of these) and secondary ions consisting of, for example, Cr, P, and O (e.g., CrPO2 + , CrPO4 -Peaks derived from at least one of the above are detected.

[0094] The amount of the acid-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of the above-mentioned chromate treatment, 2 The amount of chromate compound is about 0.5 to 50 mg, preferably 1.0 to 4 The phosphorus content is preferably about 0.0 mg, the phosphorus amount of the phosphorus compound is about 0.5 to 50 mg, preferably about 1.0 to 40 mg, and the aminated phenol polymer is about 1.0 to 200 mg, preferably about 5.0 to 150 mg.

[0095] The thickness of the acid-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 to 100 nm, and even more preferably about 1 to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-fusible resin layer. The thickness of the acid-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy.

[0096] The chemical conversion treatment is carried out by applying a solution containing a compound used to form an acid-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer is 70 to 200° C. In addition, before the chemical conversion treatment is carried out on the barrier layer, the barrier layer may be subjected to a degreasing treatment in advance by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, the chemical conversion treatment of the surface of the barrier layer can be carried out more efficiently.

[0097] [Thermofusible resin layer 4] In the battery packaging material of the present invention, the heat-sealable resin layer 4 corresponds to the innermost layer, and is a layer that seals the battery element by heat-sealing the heat-sealable resin layers together during assembly of the battery.

[0098] The resin component used in the heat-sealable resin layer 4 is not particularly limited as long as it is heat-sealable, and examples thereof include polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin. That is, the resin constituting the heat-sealable resin layer 4 may or may not contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The presence of a polyolefin skeleton in the resin constituting the heat-sealable resin layer 4 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, it is found that the maleic anhydride-modified polyolefin has a peak at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0099] Specific examples of the polyolefin include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and ethylene-butene-propylene terpolymers. Among these polyolefins, polyethylene and polypropylene are preferable.

[0100] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these polyolefins, preferred are cyclic alkenes, and more preferred are norbornene. Styrene can also be used as a constituting monomer.

[0101] The carboxylic acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of the polyolefin with a carboxylic acid. Examples of the carboxylic acid used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0102] The carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or its anhydride to the cyclic polyolefin. The cyclic polyolefin to be modified with the carboxylic acid is the same as described above. The carboxylic acid used for the modification is the same as that used for the modification of the polyolefin.

[0103] Among these resin components, preferred are carboxylic acid-modified polyolefins; more preferred are carboxylic acid-modified polypropylenes.

[0104] The thermally adhesive resin layer 4 may be formed of one type of resin component alone, or may be formed of a blend polymer of two or more types of resin components. Furthermore, the thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resin components.

[0105] The heat-sealable resin layer 4 may contain a lubricant. The lubricant present on the surface of the heat-sealable resin layer 4 may be a lubricant exuded from the resin constituting the heat-sealable resin layer 4, or may be a lubricant applied to the surface of the heat-sealable resin layer 4. When the heat-sealable resin layer 4 contains a lubricant, the moldability of the battery packaging material can be improved. The lubricant is not particularly limited, and a known lubricant can be used, for example, the lubricant exemplified in the above-mentioned base layer 1. The lubricant may be used alone or in combination of two or more kinds. The amount of the lubricant present on the surface of the heat-sealable resin layer 4 is not particularly limited, and from the viewpoint of improving the moldability of the electronic packaging material, it is preferably 10 to 50 mg / m 2 degree, More preferably, it is 15 to 40 mg / m 2 The degree of

[0106] The thickness of the heat-sealable resin layer 4 is not particularly limited as long as it functions as a heat-sealable resin layer, but may be, for example, about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. For example, when the thickness of the adhesive layer 5 described below is 10 μm or more, the thickness of the heat-sealable resin layer 4 is preferably about 85 μm or less, and more preferably about 15 to 65 μm. For example, when the thickness of the adhesive layer 5 described below is less than 10 μm or when the adhesive layer 5 is not provided, the thickness of the heat-sealable resin layer 4 is preferably about 20 μm or more, and more preferably about 35 to 85 μm.

[0107] [Adhesive layer 5] In the battery packaging material of the present invention, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 and the heat-sealable resin layer 4 in order to firmly bond them together.

[0108] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The adhesive mechanism, the type of adhesive component, and the like of the adhesive used to form the adhesive layer 5 may be the same as those of the adhesive exemplified for the adhesive layer 2. The resin used to form the adhesive layer 5 may also be a polyolefin such as polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, or carboxylic acid-modified cyclic polyolefin exemplified for the heat-sealable resin layer 4. From the viewpoint of excellent adhesion between the barrier layer 3 and the heat-sealable resin layer 4, the polyolefin is preferably a carboxylic acid-modified polyolefin, and more preferably a carboxylic acid-modified polypropylene. That is, the resin constituting the adhesive layer 5 may or may not contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The resin constituting the adhesive layer 5 may contain a polyolefin skeleton, and can be analyzed by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, the wavelength of the maleic anhydride-modified polyolefin is 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0109] From the viewpoint of improving the adhesion between the barrier layer 3 (or the acid-resistant film) and the heat-fusible resin layer 4, the adhesive layer 5 preferably contains an acid-modified polyolefin. The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component such as a carboxylic acid. Examples of the acid component used for modification include carboxylic acids or their anhydrides, such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride. Examples of the polyolefin to be modified include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); and terpolymers of ethylene-butene-propylene. Among these polyolefins, polyethylene and polypropylene are preferable.

[0110] In the adhesive layer 5, among the acid-modified polyolefins, particularly maleic anhydride-modified polyolefins, and further maleic anhydride-modified polypropylenes are preferred.

[0111] Furthermore, from the viewpoint of obtaining a battery packaging material having excellent shape stability after molding while reducing the thickness of the battery packaging material, the adhesive layer 5 is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include those mentioned above.

[0112] The adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. The adhesive layer 5 is preferably at least one selected from the group consisting of a urethane resin, an ester resin, and an epoxy resin, and is more preferably a urethane resin and an epoxy resin. As the ester resin, for example, an amide ester resin is preferable. The amide ester resin is generally produced by the reaction of a carboxyl group and an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition containing at least one of these resins and the acid-modified polyolefin. In addition, if unreacted compounds such as a compound having an isocyanate group, a compound having an oxazoline group, or a curing agent such as an epoxy resin remain in the adhesive layer 5, the presence of the unreacted compounds can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.

[0113] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 3 (or acid-resistant film), the heat-fusible resin layer 4, and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group, a curing agent having an epoxy group, and a urethane resin. The fact that the adhesive layer 5 is a cured product of a resin composition containing these curing agents can be confirmed by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), and other methods.

[0114] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the acid-resistant film and the adhesive layer 5, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of the polyfunctional isocyanate curing agent include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers.

[0115] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5.

[0116] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.

[0117] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 (or the acid-resistant film) and the adhesive layer 5.

[0118] The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and even more preferably about 200 to 800. In the present invention, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.

[0119] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.

[0120] The ratio of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 (or the acid-resistant film) and the adhesive layer 5.

[0121] In the present invention, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the epoxy resin each function as a curing agent.

[0122] The carbodiimide curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). As the carbodiimide curing agent, a polycarbodiimide compound having at least two carbodiimide groups is preferable.

[0123] From the viewpoint of improving the adhesion between the barrier layer 3 and the thermally adhesive resin layer 4 by the adhesive layer 5, the curing agent may be composed of two or more kinds of compounds.

[0124] The content of the curing agent in the resin composition forming the adhesive layer 5 is preferably in the range of approximately 0.1 to 50 mass%, more preferably in the range of approximately 0.1 to 30 mass%, and even more preferably in the range of approximately 0.1 to 10 mass%.

[0125] Furthermore, the adhesive layer 5 can also be suitably formed using, for example, an adhesive. Examples of the adhesive include an adhesive formed from an adhesive composition that contains a non-crystalline polyolefin resin (A) having a carboxyl group, a polyfunctional isocyanate compound (B), and a tertiary amine (C) having no functional group that reacts with the polyfunctional isocyanate compound (B), and contains the polyfunctional isocyanate compound (B) in an amount of 0.3 to 10 moles of isocyanate groups per mole of carboxyl groups in total, and contains the tertiary amine (C) in an amount of 1 to 10 moles per mole of carboxyl groups in total. Further, examples of the adhesive include an adhesive composition formed from a styrene-based thermoplastic elastomer (A), a tackifier (B), and a polyisocyanate (C), in which the styrene-based thermoplastic elastomer (A) and the tackifier (B) total 100% by weight, and the styrene-based thermoplastic elastomer (A) contains 20 to 90% by weight and the tackifier (B) contains 10 to 80% by weight, the styrene-based thermoplastic elastomer (A) has 0.003 to 0.04 mmol / g of active hydrogen derived from an amino group or a hydroxyl group, the active hydrogen derived from the functional group of the tackifier (B) is 0 to 15 moles per mole of the active hydrogen derived from the styrene-based thermoplastic elastomer (A), and the polyisocyanate (C) contains an isocyanate group in a range of 3 to 150 moles per mole of the total of the active hydrogen derived from the styrene-based thermoplastic elastomer (A) and the active hydrogen derived from the tackifier (B).

[0126] The thickness of adhesive layer 5 is not particularly limited as long as it functions as an adhesive layer, and may be, for example, about 50 μm or less, about 40 μm or less, preferably about 30 μm or less, more preferably about 20 μm or less, and even more preferably about 5 μm or less. The lower limit may be about 0.1 μm or more, about 0.5 μm or more, and about 10 μm or more. The thickness range is preferably about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, about 0.5 to 5 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, and about 10 to 20 μm. More specifically, when an adhesive exemplified in the adhesive layer 2 is used, the thickness is preferably about 2 to 10 μm, more preferably about 2 to 5 μm. When a resin exemplified in the heat-fusible resin layer 4 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When a cured product of an acid-modified polyolefin and a curing agent is used, the thickness is preferably about 30 μm or less, more preferably about 0.1 to 20 μm, and even more preferably about 0.5 to 5 μm. When the adhesive layer is formed from the adhesive composition described above, the thickness after drying and curing is 1 to 30 g / m 2 In addition, when the adhesive layer 5 is an acid-modified polyimide, In the case of a cured product of a resin composition containing a polyolefin and a curing agent, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating or the like.

[0127] As described later, in producing the laminate constituting the battery packaging material of the present invention, a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 in this order on the barrier layer 3 can be used in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated by co-extruding the adhesive layer 5 and the heat-sealable resin layer 4 on the barrier layer 3. That is, in the battery packaging material of the present invention, the adhesive layer and the heat-sealable resin layer can be a co-extruded laminate.

[0128] 3. Manufacturing method of battery packaging material The method for producing the battery packaging material of the present invention is not particularly limited as long as a laminate having layers of a predetermined composition can be obtained. The method for producing the battery packaging material includes, for example, a step of obtaining a laminate by laminating at least a substrate layer, a barrier layer, and a heat-sealable resin layer located on the outermost surface in this order, the outermost surface of the substrate layer being constituted by a polyester film layer, and the polyester film being a polyester film, and the total reflection method of Fourier transform infrared spectroscopy is used to obtain infrared absorption spectra in 18 directions at intervals of 10° from 0° to 180° on the surface of the polyester film, and the infrared absorption spectrum of the polyester film having a wavelength of 1340 cm -1 Absorption peak intensity Y 1340 And, 1410cm -1 Absorption peak intensity Y 1410 Ratio to (Y 1340 / Y 1410 ) maximum value Y max and the minimum value Y min Ratio of surface orientation (Y max / Y min ) is less than 1.4.

[0129] An example of a method for producing the battery packaging material of the present invention is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used for forming the adhesive layer 2 is applied and dried on the base layer 1 or on the barrier layer 3, the surface of which has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then the barrier layer 3 or the base layer 1 is laminated and the adhesive layer 2 is cured.

[0130] Next, the adhesive layer 5 and the heat-fusible resin layer 4 are laminated in this order on the barrier layer 3 of the laminate A. For example, there may be mentioned (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 on the barrier layer 3 of the laminate A by co-extruding them (co-extrusion lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, (3) a method of laminating an adhesive for forming the adhesive layer 5 on the barrier layer 3 of the laminate A by an extrusion method or a solution coating, drying at a high temperature, and further baking, and laminating a heat-sealable resin layer 4 previously formed into a sheet-like film on this adhesive layer 5 by a thermal lamination method, and (4) a method of laminating the laminate A and the heat-sealable resin layer 4 via the adhesive layer 5 while pouring a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-sealable resin layer 4 previously formed into a sheet-like film (sandwich lamination method), and the like.

[0131] As described above, a laminate is formed consisting of the base layer 1, the adhesive layer 2 provided as necessary, the barrier layer 3 whose surface is chemically treated as necessary, the adhesive layer 5, and the heat-fusible resin layer 4, and in order to strengthen the adhesiveness of the adhesive layer 2 or the adhesive layer 5, the laminate may be subjected to a heat treatment such as a hot roll contact type, a hot air type, a near infrared type, or a far infrared type. Examples of the conditions for such a heat treatment include a temperature of about 150 to 250° C. for about 1 to 5 minutes.

[0132] In the battery packaging material of the present invention, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, in order to improve or stabilize the film-forming properties, lamination processing, suitability for secondary processing of the final product (pouching, embossing), etc.

[0133] 4. Applications of battery packaging materials The battery packaging material of the present invention is used for a package for hermetically housing battery elements such as a positive electrode, a negative electrode, and an electrolyte. That is, a battery element including at least a positive electrode, a negative electrode, and an electrolyte can be housed in a package formed from the battery packaging material of the present invention to form a battery. The battery packaging material of the present invention is suitably used in applications in which printing is performed on the surface of the polyester film layer located on the outermost surface.

[0134] Specifically, a battery element having at least a positive electrode, a negative electrode, and an electrolyte is covered with the battery packaging material of the present invention in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the battery element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to seal the battery element, thereby providing a battery using the battery packaging material. When a battery element is housed in a package formed from the battery packaging material of the present invention, the package is formed so that the heat-sealable resin portion of the battery packaging material of the present invention is on the inside (the surface in contact with the battery element). The infrared absorption spectrum and the arithmetic mean roughness Ra on the surface of the polyester film layer can be measured by obtaining the battery packaging material from a battery and measuring the polyester film layer of the obtained battery packaging material. However, the infrared absorption spectrum and the arithmetic mean roughness Ra of the battery packaging material obtained from the battery are measured on the battery packaging material of the peripheral flange of the battery (the portion where the heat-sealable resin layers are heat-sealed to each other) or a portion other than the side portion (preferably the top or bottom surface of the battery).

[0135] In the present invention, a battery having a printed surface on a polyester film layer can be manufactured by a method including a step of housing a battery element including at least a positive electrode, a negative electrode, and an electrolyte in a package formed from the battery packaging material of the present invention, and a step of printing on the surface of the polyester film layer located on the outermost surface at least either before or after the housing step. That is, the battery of the present invention can be a battery having a printed portion on the surface. The printed portion is a portion on the surface of the battery on which a barcode, pattern, letter, symbol, etc. is printed.

[0136] In the battery packaging material of the present invention, when the printability of the polyethylene terephthalate film surface is evaluated under the following conditions, the radius of the dots forming the printed portion is preferably 130 μm or more, 135 μm or more, 140 μm or more, and 151 μm or less, 149 μm or less, and the preferred range of the radius is about 130 to 151 μm, about 130 to 149 μm, about 135 to 151 μm, about 135 to 149 μm, about 140 to 151 μm, about 140 to 149 μm. When the radius of the dots satisfies such a value, it can be evaluated as having excellent printability. Specifically, prints such as barcodes, patterns, characters, and symbols are formed by a collection of ink dots, and when the radius of the dots forming the printed portion satisfies the above value, the radius of the dots is not too small or too large, and the desired printing can be appropriately performed.

[0137] In addition, in the battery packaging material of the present invention, when the printability of the surface of the polyethylene terephthalate film is evaluated under the following conditions, the circularity of the dots forming the printed portion is preferably 0.725 or more. The closer the circularity of the printed portion is to 1, the more excellent the printability can be evaluated. Specifically, when the circularity of the dots forming the printed portion satisfies the above-mentioned value, the dots are not distorted and the desired printing can be performed appropriately.

[0138] <Evaluation of printability of polyethylene terephthalate film surface> In an environment of 24°C temperature and 50% relative humidity, ink is dropped onto the surface of the polyethylene terephthalate film of each battery packaging material prepared above using an inkjet printer (9040 (1.1M head) manufactured by Markem Image Co., Ltd.) and dried for 10 seconds. Next, the printability of the polyethylene terephthalate film surface is evaluated based on the radius and circularity of the dots in the printed area formed on the polyethylene terephthalate film surface. The printing setting conditions are ink viscosity: 3.4 cps, temperature: 34°C, pressure: 270 bar, nozzle size: diameter 50 μm, resolution (dot density): 115 dpi. The method for measuring the radius and circularity of the dots in the printed area is as described below. The evaluation is performed in the state of the battery packaging material. In addition, the radius and circularity of the dots in the printed area are the average values ​​of N number 3. In addition, when performing the evaluation, operations such as wiping the surface of the polyethylene terephthalate film are not performed.

[0139] The distance between the print head of the inkjet printer and the surface of the polyethylene terephthalate film is 20 mm, and the ink used is 5157E standard ink.

[0140] In addition, the radius and circularity of the dots in the printed portion formed on the surface of the polyethylene terephthalate film are observed using a laser microscope (for example, a laser microscope VK-9710 manufactured by KEYENCE) at a magnification of 10 times.

[0141] (Method of measuring the radius of the dots on the printed part) The shape of the dots in the printed area dropped onto the surface of each polyethylene terephthalate film is analyzed by a three-point circle analysis using image analysis software (e.g., KEYENCE analysis software VK Analyzer Ver2.4.0.0) for the images observed with the laser microscope to determine the radius of the circle passing through the three points (= the radius of the dots in the printed area).

[0142] (Evaluation of the circularity of printed dots) The circularity of the dots in the printed area formed by ink dropped onto the surface of each polyethylene terephthalate film is measured using image analysis software (for example, Mitani Shoji's image analysis software WinROOF (Ver6.6.0)). The analysis is performed on the figure connecting the center points of the boundary pixels that make up the outline of the dot. On the WinRoof analysis screen, this value is displayed as circularity II. The circularity of the dots in the printed area is calculated using the following formula. Circularity of the printed dot = 4π × (area of ​​the dot) / (perimeter of the dot) 2

[0143] The battery packaging material of the present invention may be used for either primary or secondary batteries, but is preferably used for secondary batteries. The type of secondary battery to which the battery packaging material of the present invention is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries are suitable applications of the battery packaging material of the present invention.

[0144] 5. Polyester film The polyester film of the present invention is a polyester film used for a polyester film layer located on the outermost surface of a battery packaging material. When infrared absorption spectra are obtained for the surface of the polyester film in 18 directions at 10° intervals from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy, the polyester film of the present invention has a Y max / Y min<1.4. The specific configuration (composition, thickness, etc.) of the polyester film of the present invention is the same as that of the polyester film layer constituting the outermost surface in "2. Each layer forming the battery packaging material" above. The infrared absorption spectrum of the surface of the polyester film can be measured with only the polyester film for the surface that will be the outermost surface of the battery packaging material. The arithmetic mean roughness Ra of the polyester film can also be measured with only the polyester film for the surface that will be the outermost surface of the battery packaging material. EXAMPLES

[0145] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0146] <Production of battery packaging materials> The battery packaging materials of Examples 1 to 3 and Comparative Examples 1 to 7 were produced by the following method.

[0147] Example 1 Biaxially oriented polyethylene terephthalate film (thickness 25 μm, surface orientation degree in Table 1: Y max / Y min and arithmetic mean roughness Ra), a barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) with an acid-resistant film formed on both sides was laminated by a dry lamination method. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil, and an adhesive layer (thickness 3 μm) was formed on the aluminum foil with the acid-resistant film formed on both sides. Next, the adhesive layer on the aluminum foil and a biaxially oriented polyethylene terephthalate film were laminated, and an aging treatment was performed to produce a laminate of a base layer / adhesive layer / barrier layer. The chemical conversion treatment for forming an acid-resistant film on the aluminum foil used as the barrier layer was performed by applying a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid in an amount of 10 mg / m2 of chromium applied.2 (Dry weight) by roll coating method The aluminum foil used as the barrier layer had an acid-resistant coating containing chromium oxide and phosphate.

[0148] Next, a maleic anhydride-modified polypropylene (thickness 25 μm) as an adhesive layer and a random polypropylene (thickness 55 μm) as a heat-sealable resin layer were co-extruded onto the barrier layer of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material in which a base layer / adhesive layer / barrier layer with acid-resistant coatings on both sides / adhesive layer / heat-sealable resin layer were laminated in this order.

[0149] The analysis of the acid-resistant film was carried out as follows. First, the barrier layer and the adhesive layer were peeled off. This was done physically, without using water, organic solvents, or aqueous solutions of acids or alkalis. After the barrier layer and the adhesive layer were peeled off, the adhesive layer remained on the surface of the barrier layer, so the remaining adhesive layer was removed by etching with Ar-GCIB. The surface of the barrier layer thus obtained was subjected to analysis of the acid-resistant film using time-of-flight secondary ion mass spectrometry. As a result, Ce2PO4 + , CePO4 - etc. The secondary ions detected were composed of Ce, P, and O. The details of the measurement equipment and conditions for the time-of-flight secondary ion mass spectrometry are as follows:

[0150] Measurement equipment: ION-TOF time-of-flight secondary ion mass spectrometer TOF.SIMS5 Measurement conditions Primary ion: Bismuth cluster doubly charged ion (Bi3 ++ ) Primary ion accelerating voltage: 30 kV Mass range (m / z): 0~1500 Measurement range: 100μm×100μm Number of scans: 16 scans / cycle Number of pixels (per side): 256 pixels Etching ions: Ar gas cluster ion beam (Ar-GCIB) Etching ion accelerating voltage: 5.0 kV

[0151] Example 2 Biaxially oriented polyethylene terephthalate film (thickness 25 μm, surface orientation degree: Y max / Y min and arithmetic mean roughness Ra) was applied to the surface with a lubricant (erucamide (coating amount 6 mg / m 2 ) and polyether modified silicone oil (application amount 1mg / m 2 ) was applied (total application amount was 7 mg / m 2 Except for the above, the battery packaging material was prepared in the same manner as in Example 1. obtained.

[0152] Example 3 As the base layer, a biaxially oriented polyethylene terephthalate film (thickness 12 μm, surface orientation degree in Table 1: Y max / Y minA laminated film was prepared by laminating a biaxially oriented nylon film (having a surface roughness of 15 μm and an arithmetic mean roughness Ra) and a biaxially oriented nylon film (thickness of 15 μm) by a dry lamination method. In the laminated film, the biaxially oriented polyethylene terephthalate film and the biaxially oriented nylon film were bonded with a urethane adhesive (thickness of 3 μm after curing) using a polyol and an isocyanate curing agent. Next, a barrier layer composed of an aluminum foil (JIS H4160:1994 A8021H-O, thickness of 40 μm) provided with an acid-resistant film by performing a chemical conversion treatment on both sides was laminated on the biaxially oriented nylon film side by a dry lamination method. Specifically, a two-liquid polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil provided with an acid-resistant film, and an adhesive layer (thickness of 3 μm) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film side of the base layer were laminated, and then aging treatment was performed to produce a laminate of base layer (biaxially oriented polyethylene terephthalate film / adhesive / biaxially oriented nylon film) / adhesive layer / barrier layer with acid-resistant coatings on both sides. The aluminum foil used as the barrier layer had acid-resistant coatings containing chromium oxide and phosphate on both sides. Analysis of the acid-resistant coating on the barrier layer was performed using time-of-flight secondary ion mass spectrometry, as in Example 1. As a result, CrPO2 + , CrPO4 - Secondary ions consisting of Cr, P, and O were detected.

[0153] Next, a maleic anhydride-modified polypropylene (thickness 40 μm) as an adhesive layer and a random polypropylene (thickness 40 μm) as a heat-sealable resin layer were co-extruded onto the barrier layer of the obtained laminate, thereby laminating an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material in which a base layer / adhesive layer / barrier layer / adhesive layer / heat-sealable resin layer were laminated in this order.

[0154] Comparative Example 1 The biaxially oriented polyethylene terephthalate film of the base layer has a surface orientation degree of Y as shown in Table 1. max / Y min A battery packaging material was obtained in the same manner as in Example 3, except that a battery packaging material having a surface roughness of 0.1 mm or less and an arithmetic mean roughness Ra was used.

[0155] Comparative Example 2 A polyethylene terephthalate film and a nylon film were laminated by coextrusion to prepare a biaxially stretched laminated film. The biaxially stretched polyethylene terephthalate film (thickness 5 μm, surface orientation degree in Table 1: Y) of the laminated film constituting the base layer was max / Y min and arithmetic mean roughness Ra) and the biaxially oriented nylon film (thickness 20 μm), there is an adhesive layer (thickness 1 μm) made of polyester (polyester-based elastomer). The laminated film is made of a biaxially oriented polyethylene terephthalate film / adhesive / biaxially oriented nylon film laminated in this order. Next, a chemical conversion treatment was applied to both sides of the surface of the biaxially oriented nylon film, and a barrier layer made of an aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) with an acid-resistant film was laminated by a dry lamination method. Specifically, a two-liquid polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil with an acid-resistant film to form an adhesive layer (thickness 3 μm). Next, the adhesive layer on the barrier layer with the acid-resistant coating was laminated with the biaxially oriented nylon film side of the base layer, and then an aging treatment was performed to produce a laminate of base layer (biaxially oriented polyethylene terephthalate film / adhesive / biaxially oriented nylon film) / adhesive layer / barrier layer with acid-resistant coatings on both sides.

[0156] Next, an adhesive (2 μm thick after curing) consisting of a non-crystalline polyolefin resin having a carboxyl group and a polyfunctional isocyanate compound was applied and dried at 100° C., and the barrier layer side of the obtained laminate and a non-oriented polypropylene film (CPP, 80 μm thick) were passed between two rolls set at 60° C. to bond them together, thereby laminating an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, an aging treatment was performed to obtain a battery packaging material in which the base layer (biaxially oriented polyethylene terephthalate film / adhesive / biaxially oriented nylon film) / adhesive layer / barrier layer / adhesive layer / non-oriented polypropylene film were laminated in this order.

[0157] Comparative Example 3 The biaxially oriented polyethylene terephthalate film of the base layer has a surface orientation degree of Y as shown in Table 1. max / Y min A battery packaging material was obtained in the same manner as in Example 3, except that a battery packaging material having a surface roughness of 0.1 mm or less and an arithmetic mean roughness Ra was used.

[0158] Comparative Example 4 The biaxially oriented polyethylene terephthalate film of the base layer has a surface orientation degree of Y as shown in Table 1. max / Y min A battery packaging material was obtained in the same manner as in Example 3, except that a battery packaging material having a surface roughness of 0.1 mm or less and an arithmetic mean roughness Ra was used.

[0159] Comparative Example 5 The biaxially oriented polyethylene terephthalate film of the base layer has a surface orientation degree of Y as shown in Table 1. max / Y min A battery packaging material was obtained in the same manner as in Example 3, except that a battery packaging material having a surface roughness of 0.1 mm or less and an arithmetic mean roughness Ra was used.

[0160] Comparative Example 6 Biaxially oriented polyethylene terephthalate film (thickness 25 μm, surface orientation degree: Y max / Y min and arithmetic mean roughness Ra) was coated with a lubricant (erucamide) (coating amount 7 mg / m 2) A battery packaging material was obtained in the same manner as in Comparative Example 2.

[0161] Comparative Example 7 Biaxially oriented polyethylene terephthalate film (thickness 25 μm, surface orientation degree: Y max / Y min and arithmetic mean roughness Ra) was coated with a lubricant (erucamide) (coating amount 10 mg / m 2 Except for the above, a battery packaging material was obtained in the same manner as in Comparative Example 2. Ta.

[0162] <Measurement of surface orientation> For the biaxially stretched polyethylene terephthalate film surface (the surface opposite to the barrier layer) of each of the battery packaging materials prepared above, infrared absorption spectra were obtained in 18 directions at 10° intervals from 0° to 170° using Fourier transform infrared spectroscopy (FT-IR) attenuated total reflection (ATR). The wave number of the infrared absorption spectrum for each of the 18 directions was 1340 cm. -1 Absorption peak intensity Y 1340 (CH2 vertical vibration) and wave number 1410 cm -1 In Peak intensity Y 1410 (C=C stretching vibration) value of Y 1340 / Y 1410 Calculate the maximum value Y max and the minimum value Y min From the above, the surface orientation degree: Y max / Y min The specific conditions for measuring the infrared absorption spectrum are as follows. The results are shown in Table 1.

[0163] In addition, for Example 2 and Comparative Examples 6 and 7, the lubricant on the surface of the biaxially stretched polyethylene terephthalate film was wiped off with 2-butanone, and the degree of surface orientation was measured for the surface of the biaxially stretched polyethylene terephthalate film.

[0164] (Infrared absorption spectrum measurement conditions) Spectrometer: Nicolet iS10 FT-IR manufactured by Thermo Fisher Scientific Attachment: Single reflection ATR attachment (Seagull) Detector: MCT (Hg Cd Te) Wavenumber resolution: 8cm -1 Number of times accumulated: 128 times IRE:Ge Incident angle: 30° Polarizer: Wire grid, S-polarized Baseline: Wavenumber 1800-2000cm -1 Average intensity in the range Wave number 1340cm -1 Absorption peak intensity Y 1340 : Wave number 1335~1342cm -1 The maximum peak intensity in the range minus the baseline value Wave number 1410cm -1 Absorption peak intensity Y 1410 : Wave number 1400~1410cm -1 The maximum peak intensity in the range minus the baseline value

[0165] To obtain infrared absorption spectra in 18 directions, the sample with the exposed polyester film was placed horizontally on the sample holder and rotated by 10° each time with the Ge crystal placed on top of the sample. The incidence angle is the angle between the perpendicular line (normal line) and the incident light.

[0166] <Measurement of arithmetic mean roughness Ra of polyethylene terephthalate film surface> The arithmetic mean roughness Ra was measured for the surface of the biaxially stretched polyethylene terephthalate film (polyester film layer) constituting the outermost surface of each battery packaging material obtained above, in accordance with the method specified in JIS B 0601-2001. The arithmetic mean roughness Ra was measured using a white light interferometer NewView7300 manufactured by Zygo Corporation, with a measurement area of ​​0.22 mm square (50x objective lens, 1x zoom lens) and tilt correction (Cylinder). The arithmetic mean roughness Ra was measured in the state of the battery packaging material. Note that no operation such as wiping the surface of the polyethylene terephthalate film was performed during the measurement. The results are shown in Table 1.

[0167] <Evaluation of printability of polyethylene terephthalate film surface> In an environment of 24°C temperature and 50% relative humidity, ink was dropped onto the biaxially oriented polyethylene terephthalate film surface of each battery packaging material prepared above using an inkjet printer (9040 (1.1M head) manufactured by Markem Image Co., Ltd.) and dried for 10 seconds. Next, the printability of the biaxially oriented polyethylene terephthalate film surface was evaluated based on the radius and circularity of the dots in the printed part formed on the biaxially oriented polyethylene terephthalate film surface. The printing setting conditions were ink viscosity: 3.4 cps, temperature: 34°C, pressure: 270 bar, nozzle size: diameter 50 μm, resolution (dot density): 115 dpi. The method for measuring the radius and circularity of the dots in the printed part is as described below. The evaluation was performed in the state of the battery packaging material. In addition, the radius and circularity of the dots in the printed part were the average values ​​of N number 3. In addition, when performing the evaluation, operations such as wiping the surface of the polyethylene terephthalate film were not performed. The results are shown in Table 1.

[0168] The distance between the print head of the inkjet printer and the surface of the biaxially oriented polyethylene terephthalate film was 20 mm, and 5157E standard ink was used.

[0169] Further, the radius and circularity of the dots in the printed portion formed on the surface of the biaxially stretched polyethylene terephthalate film were observed using a laser microscope (Keyence Laser Microscope VK-9710) at a magnification of 10. For reference, images of the printed portion formed on the surface of the biaxially stretched polyethylene terephthalate film observed with a laser microscope for Example 2 and Comparative Example 7 are shown in Figure 4 (Example 2) and Figure 5 (Comparative Example 7), respectively.

[0170] (Method of measuring the radius of the dots on the printed part) The shape of the dots printed on the surface of each biaxially oriented polyethylene terephthalate film was analyzed using the KEYENCE analysis software VK Using Analyzer Ver2.4.0.0, the radius of the circle passing through the three points (= the radius of the dot in the printed area) was calculated by a three-point circle analysis. The results are shown in Table 1.

[0171] (Evaluation of the circularity of printed dots) The circularity of dots in the printed portion formed by ink dropped on the surface of each biaxially oriented polyethylene terephthalate film was measured using image analysis software WinROOF (Ver6.6.0) manufactured by Mitani Shoji. The analysis was performed on a figure connecting the center points of the boundary pixels that form the outline of the dot. On the analysis screen of WinRoof, this value is displayed as circularity II. The circularity of dots in the printed portion is calculated by the following formula. The circularity of dots in the printed portion was evaluated according to the following criteria. The results are shown in Table 1. For reference, the measured values ​​of the circularity of dots in the printed portion for Example 2 (FIG. 4) and Comparative Example 7 (FIG. 5) are shown in Table 1. Circularity of the printed dot = 4π × (area of ​​the dot) / (perimeter of the dot) 2 A: The circularity of the dots in the printed area is 0.725 or more, and the dots in the printed area have a beautiful circular shape on the surface of the biaxially oriented polyethylene terephthalate film. B: The circularity of the dots in the printed portion is 0.700 or more and less than 0.725, and the dots in the printed portion have an irregular circular shape on the surface of the biaxially oriented polyethylene terephthalate film.

[0172] [Table 1]

[0173] In the battery packaging materials of Examples 1 to 3, the polyester film layer constituting the outermost surface is a polymer having the formula: Y max / Y min <1.4, the radius of the dots in the printed portion was small, and the circularity of the dots in the printed portion was also evaluated as excellent, indicating excellent printability. The results of Examples 1 to 3 show that excellent printability is exhibited regardless of whether or not a lubricant is present on the surface of the polyester layer. In contrast, the battery packaging materials of Comparative Examples 1 to 7 have a polyester film layer constituting the outermost surface that satisfies the formula: Y max / Y min The relationship of <1.4 was not satisfied, and the radius of the dots in the printed portion was large, or the evaluation of the circularity of the dots in the printed portion was poor. For example, in Comparative Example 7, the radius of the dots in the printed portion was small, but the circularity was small at 0.723, and the dots in the printed portion had an irregular circular shape on the surface of the polyethylene terephthalate film layer, and the printability was poor (see FIG. 5). In Comparative Example 6, a lubricant was present on the surface of the polyester layer, and the radius of the dots in the printed portion was similar to that of Comparative Example 2, but the radius of the dots in the printed portion was larger than those in Examples 1 to 3, and the printability was poor. In Comparative Example 7, in which the amount of lubricant was increased more than in Comparative Example 6, the radius of the dots in the printed portion was small as described above, but the dots in the printed portion had an irregular circular shape, and the printability was poor. [Explanation of symbols]

[0174] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer

Claims

[Claim 1] The laminate includes at least a substrate layer located on the outermost surface, a barrier layer, and a heat-sealable resin layer in this order, The outermost surface of the base layer is constituted by a polyester film layer, A battery packaging material, wherein when infrared absorption spectra are obtained for the surface of the polyester film layer in 18 directions at 10° increments from 0° to 170° using the total reflection method of Fourier transform infrared spectroscopy, the following formula is satisfied: Y max / Y min <1.4 Y max In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410 cm -1 Absorption peak intensity Y 1410 It is the maximum value among the values ​​divided by. Y min In each of the 18 directions, the infrared absorption spectrum wave number is 1340 cm -1 Absorption peak intensity Y 1340 , wave number 1410 cm -1 Absorption peak intensity Y 1410 It is the minimum value among the values ​​divided by.

Citation Information

Patent Citations

  • Layered package material, outer package material for battery, and the battery

    JP2008287971A